When books went to war [large type] : the stories that helped us win World War II - Manning, Molly Guptill, 1980- (Thorndike Press large print nonfiction series., 2015)
When America entered World War II, we faced an enemy that had banned and burned over 100 million books. Outraged librarians sent donated books to our troops. The War Department joined the publishing industry in an extraordinary program: 120 million books printed in small, lightweight paperbacks. Beloved by the troops and still fondly remembered, theirs is an inspiring story.